Suppression of terpenoid synthesis in plants by a virus promotes its mutualism with vectors. (20th December 2012) - Luan, Jun‐Bo; Yao, Dan‐Mei; Zhang, Tong; Walling, Linda L.; Yang, Mei; Wang, Yu‐Jun; Liu, Shu‐Sheng
Abstract: Vectors often perform better on plants infected with pathogens, and this promotes the spread of pathogens. However, few studies have examined how plant defensive compounds mediate such mutualistic relationships. Although tobacco plants are relatively poor host plants for the whitefly Bemisia tabaci, tobacco's suitability to the whitefly was substantially increased when infected by the begomovirus Tomato yellow leaf curl China virus . The change in suitability was associated with induced terpenoid synthesis in whitefly‐infested plants and repressed terpenoid synthesis in virus‐infected plants. Elevation of terpenoid levels via exogenous stem applications reduced the performance of whiteflies. In contrast, suppression of terpenoid synthesis via gene silencing improved whitefly fitness. By integrating genomics, transcriptomics and metabolomics, this study demonstrated that virus infection depleted the terpenoid‐mediated plant defence against whiteflies, thereby favouring vector–virus mutualism. These data suggest that plant terpenoids play a key role in shaping vector–pathogen relationships.